Coloproctology - Zbar, Andrew P.; Wexner, Steven D.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2010)
Coloproctology is an essential aid for those who need a practical understanding of particularly complex procedures in this specialty. Edited and authored by outstanding surgeons in their fields, this book brings the reader expertise in surgery and management across the various conditions encountered in colorproctology, from Sigmoid Diverticulitis to colorectal cancer. Didactic in its approach, this book is key reading for trainees in coloproctology as well as senior surgical coloproctologists who wish to extend their knowledge of this important field.
Genetic Approaches to Colorectal Cancer -- Multivisceral Resection in Rectal Cancer -- Colonic Stenting -- Chemotherapy Trials for Colorectal Cancer in Advanced Disease: What$1 (Bs the Current Hypothesis? -- Current Clinical Trials in Radiotherapy for Rectal Cancer -- Quality of Life Issues and Rectal Cancer -- Managing Presacral Tumors -- Revisional Pouch Surgery -- Surgery for Fecal Incontinence -- Recurrent Rectal Cancer -- The Surgical Management of Evacutory Dysfunction -- New Approaches in Perineal Crohn$1 (Bs Disease -- Complex Anal Fistula -- Rectovaginal and Rectourethral Fistula -- Surgeon-Performed Ultrasound in Proctologic Practice -- Changing Paradigms in the Treatment of Sigmoid Diverticulitis.s
Keywords: Medicine; Gynecology; Endocrinology; Surgery; Colon (Anatomy) -- Surgery; Medicine & Public Health; Colorectal Surgery; Proctology; General Surgery; Gynecology; Surgery